2014
DOI: 10.2147/cia.s63337
|View full text |Cite
|
Sign up to set email alerts
|

Altered diastolic function and aortic stiffness in Alzheimer’s disease

Abstract: Background: Alzheimer's disease (AD) is closely linked to cardiovascular risk factors. Methods: Echocardiographic studies were performed, including left ventricular diastolic functions, left and right atrial conduction times, and arterial stiffness parameters, namely stiffness index, pressure-strain elastic modulus, and distensibility, on 29 patients with AD and 24 age-matched individuals with normal cognitive function. Results: The peak mitral flow velocity of the early rapid filling wave (E) was lower, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…In conclusion, no studies have examined cardiovascular function in the 3xTg model of AD as well as the roles of polyphenol treatment and exercise training on basic indices of cardiac and aortic function. Here, we have reported that hearts from 3xTg mice exhibit functional abnormalities in systolic and diastolic properties that are similar to those observed in patients diagnosed with dementia and AD,56,79 suggesting that the 3xTg model may be relevant for mechanistic-based investigation of AD. Further, our data show that consumption of the polyphenol resveratrol and exercise training are protective against the development of certain indices of LV dysfunction and aortic wall structure in this model.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In conclusion, no studies have examined cardiovascular function in the 3xTg model of AD as well as the roles of polyphenol treatment and exercise training on basic indices of cardiac and aortic function. Here, we have reported that hearts from 3xTg mice exhibit functional abnormalities in systolic and diastolic properties that are similar to those observed in patients diagnosed with dementia and AD,56,79 suggesting that the 3xTg model may be relevant for mechanistic-based investigation of AD. Further, our data show that consumption of the polyphenol resveratrol and exercise training are protective against the development of certain indices of LV dysfunction and aortic wall structure in this model.…”
Section: Resultssupporting
confidence: 53%
“…Indeed, LV cardiomyocytes obtained from patients with AD displayed slower relaxation velocities and prolonged calcium transients. These changes are correlated with a decline in myocardial compliance, 17 which could also explain the diastolic dysfunction recently reported in these patients. 56 A defect in relaxation, expressed as maximum velocity of relengthening time, has been reported in cardiomyocytes obtained from the APP/PS1 mouse model of AD.…”
Section: Discussionmentioning
confidence: 79%
“…El consenso científico reconoce 7 factores de riesgo que tienen una evidencia consistente de asociación con EA: diabetes, hipertensión arterial y obesidad de la mediana edad, inactividad física, depresión, tabaquismo y bajo nivel instruccional [10][11][12][13][14] . Los estudios de Norton et al 10 calcularon a nivel mundial un RAP combinado de factores asociados a EA, estimando que de los 33-35 millones de casos de demencia, 9 millones son atribuibles a los 7 factores de riesgo de la enfermedad.…”
Section: Introductionunclassified
“…The accumulated brain damage results in brain atrophy and cognitive dysfunction 30,31 . Other suggested etiologies include heart diastolic dysfunction 32 , medial temporal lobe atrophy 33 , reduced white matter integrity 34 , increased white matter hyperintensities 35 , progression of betaamyloid deposition 36 , and impaired renal function 26 .…”
mentioning
confidence: 99%